The Rise of Christian Democracy in Europe - Kalyvas, Stathis N. (Wilder House series in politics, history, and culture., 2018)
Although dominant in West European politics for more than a century, Christian Democratic parties remain largely unexplored and little understood. An investigation of how political identities and parties form, this book considers the origins of Christian Democratic "confessional" parties within the political context of Western Europe. Examining five countries where a successful confessional party emerged (Belgium, the Netherlands, Austria, Germany, and Italy) and one where it did not (France), Stathis N. Kalyvas addresses perplexing questions raised by the Christian Democratic phenomenon. How can we reconcile the religious roots of these parties with their tremendous success and resilience in secular and democratic Western Europe? Why have these parties discarded their initial principles and objectives to become secular forces governing secular societies? The author's answers reveal the way in which social and political actors make decisions based on self-interest under conditions that constrain their choices and the information they rely on-often with unintended but irrevocable consequences. Kalyvas also lays a foundation for a theory of the Christian Democratic phenomenon which would specify the conditions under which confessional parties succeed and would determine the impact of such parties, and the way they are formed, on politics and society. Drawing from political science, sociology, and history, his analysis goes beyond Christian Democracy to address issues related to the methodology of political science, the theory of party formation, the political development of Europe, the relationship between religion and politics, the construction of collective political identities, and the role of agency and contingency in politics.